2015
DOI: 10.1038/srep11170
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of silver nanoparticles into mouse spermatozoa results in poor fertilization and compromised embryo development

Abstract: Silver nanoparticles (AgNPs) have many features that make them attractive as medical devices, especially in therapeutic agents and drug delivery systems. Here we have introduced AgNPs into mouse spermatozoa and then determined the cytotoxic effects of AgNPs on sperm function and subsequent embryo development. Scanning electron microscopy and transmission electron microscopy analyses showed that AgNPs could be internalized into sperm cells. Furthermore, exposure to AgNPs inhibited sperm viability and the acroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 62 publications
0
46
0
1
Order By: Relevance
“…Furthermore, incubation of sperm with AgNPs led to dose‐dependent inhibition of viability and the acrosome reaction as well as abnormalities in sperm mitochondrial copy numbers and morphology through increased generation of intracellular ROS . Consistently, AgNP‐induced sperm abnormalities were associated with significantly decreased rates of oocyte fertilization and embryonic development . Notably, intraperitoneal injection of small AgNPs (measuring 10 nm in diameter) into mice induced higher acute toxicity, implying that the toxic effects of AgNPs are dependent on particle size and dosage.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, incubation of sperm with AgNPs led to dose‐dependent inhibition of viability and the acrosome reaction as well as abnormalities in sperm mitochondrial copy numbers and morphology through increased generation of intracellular ROS . Consistently, AgNP‐induced sperm abnormalities were associated with significantly decreased rates of oocyte fertilization and embryonic development . Notably, intraperitoneal injection of small AgNPs (measuring 10 nm in diameter) into mice induced higher acute toxicity, implying that the toxic effects of AgNPs are dependent on particle size and dosage.…”
Section: Introductionmentioning
confidence: 85%
“…Characterization of sperm and identification of potential targets, such as proteins related to acrosome integrity (Cross & Watson, ) and genes linked to freezability (Vilagran et al, ), make the use of nanoparticles interesting for applications in studies involving sperm enrichment and sorting (Feugang, ). Mesoporous silica, quantum dots, iron oxide, zinc oxide, gold, and silver nanostructures have been shown to interact with cattle, human, mouse, and pig spermatozoa (Barkalina, Jones, Kashir, et al, ; Feugang et al, ; Feugang, Youngblood, Greene, Willard, & Ryan, ; Moretti et al, ; Taylor et al, ; Yoisungnern et al, ). In the pig, Barkalina et al () observed that mesoporous silica nanoparticles (MSNPs) functionalized with polyethileneimine (PEI) and aminopropyltriethoxysilane were able to stably bind one in five boar sperm with no negative effects on the main parameters of sperm function (total and progressive motility, motion parameters, viability, acrosome morphology, or DNA fragmentation index).…”
Section: Nanotechnologymentioning
confidence: 99%
“…Characterization of sperm and identification of potential targets, such as proteins related to acrosome integrity (Cross & Watson, 1994) and genes linked to freezability (Vilagran et al, 2015), make the use of nanoparticles interesting for applications in studies involving sperm enrichment and sorting (Feugang, 2017). Mesoporous silica, quantum dots, iron oxide, zinc oxide, gold, and silver nanostructures have been shown to interact with cattle, human, mouse, and pig spermatozoa (Barkalina, Jones, Kashir, et al, 2014;Feugang et al, 2012;Feugang, Youngblood, Greene, Willard, & Ryan, 2015;Moretti et al, 2013;Taylor et al, 2015;Yoisungnern et al, 2015). In the pig, Barkalina et al (2016) (Wang, Zhao, et al, 2017).…”
mentioning
confidence: 99%
“…Wpływ nanomateriałów na płodność i zdrowie potomstwa nie został jak dotąd dokładnie przebadany. Pierwsze badania na zwierzętach wykazały, że nanocząstki projektowane, zaburzając proces spermatogenezy i obniżając parametry nasienia, wpływają na płodność męskich osobników [46][47][48][49]. Ponadto różne rodzaje nanocząstek -m.in.…”
Section: Wpływ Na Płodność I Zdrowie Potomstwaunclassified